Student participation in the construction of municipal democratic management as an element of the SME - Meire Lúcia Andrade da Silva; Thaise Luciane Nardim; Meyrivane Teixeira Santos Arraes; Alessandro Pimenta (Universidade Federal do Norte do Tocantins, 2023)
The article addresses the topic of student participation in Municipal Education. It aims to understand student participation as an element of democratic management in the Municipal Education System. With a critical perspective, it is based on empirical-documentary research. The municipal sphere proposes goals and actions towards establishing student participation through unions, within the limits of the attributions of these federated entities and towards operationalizing the PNE and the PEE (or PDE), through their Municipal Education Plans (PMEs) and Pedagogical Political Projects (PPPs) of the school units. The various instances responsible for promoting education encounter difficulties in operationalizing and consolidating student participation, either through Student Unions or other forms of participation. Difficulty that, in part, arises from the resistance of individual managers. The investigation presents possibilities for student participation. It highlights the democratic value of the inducing role of the PNE and SMEs, but it also imposes the urgency of the action of extrastate organizations, oriented to form, accompany, monitor and evaluate the implantation processes, the instrumentalization and the validity of constitutive elements of the Municipal Systems of Teaching/Education.